Amperometric biosensor for ascorbic acid - Tomita, Inês Noriko; Manzoli, Alexandra; Fertonani, Fernando Luis; Yamanaka, Hideko (Eclética Química, 2005)
A L-ascorbic acid biosensor based on ascorbate oxidase has been developed. The enzyme was extracted from the mesocarp of cucumber (Cucumis sativus) by using 0.05 mol L -1 phosphate buffer, pH 5.8 containing 0.5 mol L -1 NaCl. After the dialysis versus phosphate buffer 0.05 mol L -1 pH 5.8, the enzyme was immobilized onto nylon net through glutaraldehyde covalent bond. The membrane was coupled to an O 2 electrode and the yielding reaction monitored by oxygen depletion at -600 mV using flow injection analysis optimized to 0.1 mol L -1 phosphate buffer pH 5.8, as the carrier solution and flow-rate of 0.5 mL min -1 . The ascorbic acid calibration curve was linear from 1.2x10 -4 to 1.0x10 -3 mol L -1 . The evaluation of biosensor lifetime leads to 500 injections. Commercial pharmaceutical samples were analyzed with the proposed method and the results were compared with those obtained by high-performance liquid chromatography (HPLC).